2020
DOI: 10.3390/jmse8010056
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Linear BEM–FEM Coupled Scheme for the Performance of Flexible Flapping-Foil Thrusters

Abstract: Recent studies indicate that nature-inspired thrusters based on flexible oscillating foils show enhanced propulsive performance. However, understanding the underlying physics of the fluid–structure interaction (FSI) is essential to improve the efficiency of existing devices and pave the way for novel energy-efficient marine thrusters. In the present work, we investigate the effect of chord-wise flexibility on the propulsive performance of flapping-foil thrusters. For this purpose, a numerical method has been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…However, the weak coupling approach does not permit the prediction of the phase lag between the prescribed flapping motions and the wing's response in terms of bending deformation; which would improve the prediction capabilities of the computational tool significantly. In a recent work by the author's [15] the fully coupled 2-D BEM-FEM scheme is proposed for the hydroelastic analysis of flapping-foil thrusters and it is found to be in excellent agreement with experimental data found in the literature. Finally, the tools developed for the present work serve as the building blocks for the fully coupled 3-D BEM-FEM scheme for hydroelastic analysis and optimization that is currently under study.…”
Section: Introductionsupporting
confidence: 52%
“…However, the weak coupling approach does not permit the prediction of the phase lag between the prescribed flapping motions and the wing's response in terms of bending deformation; which would improve the prediction capabilities of the computational tool significantly. In a recent work by the author's [15] the fully coupled 2-D BEM-FEM scheme is proposed for the hydroelastic analysis of flapping-foil thrusters and it is found to be in excellent agreement with experimental data found in the literature. Finally, the tools developed for the present work serve as the building blocks for the fully coupled 3-D BEM-FEM scheme for hydroelastic analysis and optimization that is currently under study.…”
Section: Introductionsupporting
confidence: 52%
“…with emphasis on the effects of a superposition of chordwise and spanwise bending on the propulsive performance of the thruster. The phase differences that contribute to efficiency enhancement for this setup have been determined in previous work by the authors (Anevlavi, Filippas and Belibassakis 2023), as ψc=180deg and ψb=0deg respectively. The frequency of motions is kept the same.…”
Section: Optimal Thruster With Active Chordwise/spanwise Bendingmentioning
confidence: 89%
“…The code includes GP-GPU acceleration features targeting the computationally demanding numerical integration for the calculation of the induced coefficients using the processors of an NVIDIA graphics card and the CUDA API, which significantly reduces the computational time of the simulation. The present solver that has been used in a previous work by the authors (Anevlavi, Filippas and Belibassakis 2023),  enables numerical calculation of the wing body velocities using backward finite differences with GPU parallelization.  re-generates the surface mesh at each time-instance to simulate a deforming wing  re-calculates of the induced coefficients (DtN) matrix at each time-step  calculates the propulsive performance metrics targeting flapping-foil thrusters…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have taken place, either experimental [8,9] or numerical (a collection can be found here in [4]), showing the applicability of these devices and highlighting their advantages and disadvantages over conventional devices. Incorporating chord-wise flexibility also seems promising as increases in performance are significant, as shown in [10]. Importantly, this device can be simplified by attaching the heaving degree of freedom (DOF) to a spring and damper, and imposing the motion of the pitching DOF, creating the semi-passive flapping foil [11].…”
Section: Introductionmentioning
confidence: 99%